Obscene History. The Two Sedlmayrs (Studia austriaca, 2016)
The following article proposes a new interpretation of Hans Sedlmayr’s politics, which thereby achieves a more successful understanding of his work. Seeking to reconcile progressive and totalitarian elements of Sedlmayr’s thought, his stance is characterized as «National Bolshevist». Consistent with this view, there are two phases detected in Sedlmayr’s outlook, an early cosmopolitan phase and a later more symptomological cultural criticism. Seeking to nuance the complexity of politics in the 1930s, in the end it is nevertheless argued that it is impossible to link tightly Sedlmayr’s historical pronouncements with his politics.